2012
DOI: 10.1039/c1sm06870a
|View full text |Cite
|
Sign up to set email alerts
|

Patterned flexoelectric instability in a bent-core nematic liquid crystal

Abstract: We examine here the Bobylev-Pikin flexoelectric instability in an initially planar monodomain of a bent-core nematic liquid crystal, which is negative in conductivity and dielectric anisotropies. Experiments employing dc excitation reveal the domain density to be linear in field, as predicted; however, the instability threshold has a negative temperature coefficient indicating the effective flexomodulus as nonquadratic in order parameter. The dc threshold is also determined as a function of simultaneously acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
4
18
0
Order By: Relevance
“…This behaviour is in accordance with previous findings on FD in other nematics [16,17]. For low frequencies of the ac voltage component (f = 2 Hz, Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This behaviour is in accordance with previous findings on FD in other nematics [16,17]. For low frequencies of the ac voltage component (f = 2 Hz, Fig.…”
Section: Resultssupporting
confidence: 82%
“…Experimental studies on electro-optics in nematics at combined ac+dc driving are so far very scarce. E.g., the dc threshold of FD was found to increase upon superposing ac voltage in a calamitic [16] as well as in a bent-core nematic [17]; however, the instabilities at pure ac driving or at a small dc bias voltage have not been studied. Combined driving was also applied for the nematic 5CB (4-pentyl-4'-cyanobiphenyl) having ε a > 0 and σ a > 0 and thus exhibiting nonstandard EC [18].…”
Section: Introductionmentioning
confidence: 99%
“…[44] Bent-core nematics, due to the combination of their molecular shape with a transverse component of their dipole moment, are ideal candidates for compounds with a large flexoelectric response. Indeed, determination of the flexoelectric coefficient of some BCN materials from the observed flexoelectric domains [45] and flexoelectro-optic effect [46] confirmed this theoretical anticipation. Moreover, it was reported that under certain conditions (e.g.…”
Section: Introductionmentioning
confidence: 75%
“…[33] Bent-core nematic (BCN) systems (including mixtures of bent-core and rod-like molecules) may also exhibit EC patterns. [34][35][36][37][38][39][40][41][42][43][44][45] The patterns reported so far can mostly be classified as non-standard EC, however, with some characteristics substantially different from those in calamitic LCs.…”
Section: Introductionmentioning
confidence: 99%
“…The bentcore nematics (BCNs) studied so far mostly exhibit various nonstandard EC patterns [7][8][9][10][11][12][13][14][15][16][17][18][19][20], whose characteristics may substantially differ from those in calamitic LCs. Moreover, there are some unprecedented scenarios, like prewavy patterns at ultrahigh ( / > 50 kHz) frequencies with negative slope of Uc(f), which have been found so far only in BCN compounds [7,[11][12][13], These banana-specific features still wait for explanation.…”
Section: Introductionmentioning
confidence: 99%